Therapeutic use of VR serious games in the treatment of negative schizophrenia symptoms : a systematic review - Miranda, Beatriz (2022)
Schizophrenia is a chronic brain disorder that affects 1 in every 300 people worldwide. This study intended to perform a systematic review to describe the state-of-the-art of interventions involving patients with negative symptoms of schizophrenia that use Virtual Reality (VR) games as a complement to therapy, and to analyze the key features of such games. Literature research was conducted in three databases, namely, the Institute of Electrical and Electronics Engineers (IEEE), Scopus, and PubMed, to identify relevant publications dated from 2010 to 2021. Of the initial 74 publications found, only 11 satisfied the eligibility requirements and were included in this study. The results were then organized and displayed in a flow diagram. Overall, the results from the studies suggest that the use of VR in therapies enables an increase in social skills and a decrease in anxiety symptoms. The use of such technology in therapy has proven to be effective, although it still lacks features to provide better long-term results.